Pengembangan Media Pembelajaran Berbasis Chemo-Edutainment Melalui Model Instructional Games Pada Materi Konfigurasi Elektron - Evi Sapinatul Bahriah; Tonih Feronika; Hari Suharto (Jurnal Riset Pendidikan Kimia (JRPK), 2017)
This study aims to produce instructional media based on chemo-edutainment through a model of instructional games on electron configuration and to discover the response of teachers and students on developed instructional media. The research method is qualitative descriptive with three stages. They are pre-production stage, production, and post-production. Data were analyzed descriptively. On the pre-production stage, the design of instructional media was produced based on chemo-edutainment that had been integrated with the model from instructional games. On the production stage, instructional media that had been validated by four lecturers was produced. On the post-production, the instructional media experimented on three chemistry teachers and 35 public senior high school' students in Tangerang. The product was responded based on aspects of quality of content, quality of technical, and packaging of teaching materials. The result of this study shows that the developed instructional media had educational value and had entertaining and enjoyable characteristic for the user. The defined experiment's result obtained 84.09% of teacher and 82.88% of student response are an excellent category. Keywords: Instructional Media, Chemo-Edutainment, Instructional Games, Electron Configuration